Modelling of Transient CO2/Water Flow in Wellbore considering Multiple Mass and Heat Transfer - Xinxin Zhao; Xiangzhen Yan; Xiaohui Sun; Qing Zhao; Hongwei Jiang; Yonghai Gao; Guang Yang (Geofluids)
A transient fully coupled model is proposed to investigate the two-phase flow of CO2 and water-based fluid in a wellbore, considering the complex mass and heat transfer in different flow patterns and dynamic coupling between the wellbore and reservoir. Based on mass conservation, momentum, and energy balance, the model employs a state-of-the-art equation of state and transport models to analyze the variations of multiphase flow behaviors and CO2 properties in a wellbore. Applied in the scenario of a drilled gas kick, the proposed model is used to simulate the processes of gas migration and two-phase flow in the wellbore. The results indicate that the CO2 solubility increases gradually with the increment of depth, the trend of which shows an abrupt change in 500-1000 m due to the phase transition of CO2. During kick development, the fronts of free gas and dissolved gas increase almost linearly with time. Through a comparison of CO2 and CH4 kicks, gas dissolution is found to significantly suppress the development process of CO2 kick. The error in kick prediction can reach 42% if the effect of gas dissolution is neglected. However, it can be neglected for CH4 kick.